The Influence of Na+, K+-ATPase on Glutamate Signaling in Neurodegenerative Diseases and Senescence - Kinoshita, Paula F.; Leite, Jacqueline A.; Orellana, Ana Maria M.; Vasconcelos, Andrea R.; Quintas, Luis E. M.; Kawamoto, Elisa M.; Scavone, Cristoforo (Frontiers in Physiology, 2016)
Decreased Na+,K+-ATPase (NKA) activity causes energy deficiency, which is commonly observed in neurodegenerative diseases. The NKA is constituted of three subunits: α, β and γ, with four distinct isoforms of the catalytic α subunit (α1-4). Genetic mutations in the ATP1A2 gene and ATP1A3 gene, encoding the α2 and α3 subunit isoforms, respectively can cause distinct neurological disorders, concurrent to impaired NKA activity. Within the central nervous system (CNS), the α2 isoform is expressed mostly in glial cells and the α3 isoform is neuron-specific. Mutations in ATP1A2 gene can result in familial hemiplegic migraine (FHM2), while mutations in the ATP1A3 gene can cause Rapid-onset dystonia-Parkinsonism (RDP) and alternating hemiplegia of childhood (AHC), as well as the cerebellar ataxia, areflexia, pescavus, optic atrophy and sensorineural hearing loss (CAPOS) syndrome. Data indicates that the central glutamatergic system is affected by mutations in the α2 isoform, however further investigations are required to establish a connection to mutations in the α3 isoform, especially given the diagnostic confusion and overlap with glutamate transporter disease. The age-related decline in brain α2/3 activity may arise from changes in the cyclic guanosine monophosphate (cGMP) and cGMP‐dependent protein kinase (PKG) pathway. Glutamate, through nitric oxide synthase (NOS), cGMP and PKG, stimulates brain α2/3 activity, with the glutamatergic N-methyl-D-aspartate (NMDA) receptor cascade able to drive an adaptive, neuroprotective response to inflammatory and challenging stimuli, including amyloid‐β. Here we review the NKA, both as an ion pump as well as a receptor that interacts with NMDA, including the role of NKA subunits mutations. Failure of the NKA-associated adaptive response mechanisms may render neurons more susceptible to degeneration over the course of aging.